ANALISIS KANDUNGAN BAHAN ORGANIK TANAH DI KEBUN TRADISIONAL DESA SEREH KABUPATEN KEPULAUAN TALAUD - Riansen Alva Nangaro; Zetly E, Tamod; Tilda Titah (Universitas Sam Ratulangi, 2020)
ABSTRACTThe objectives of this study were to determine the content of soil organic matterin traditional gardens in Sereh Village, Lirung District, Talaud Islands Regency. Thisresearch was conducted in the Traditional Garden of Sereh Village and the Laboratoryof Chemistry and Soil Fertility, Faculty of Agriculture, Unsrat for 1 month. Thisresearch uses a survey method. Sampling was carried out using the sampling methodin groups / cluster sampling (CS). Soil samples were taken with a depth of 0-50 cm,50-100 cm, and> 100 cm under the clove, nutmeg and coconut plants. The chemicalparameters analyzed were; organic matter content (Walkley and Black Method). Soilsamples were analyzed at the Laboratory of Chemistry and Soil Fertility, Departmentof Soil, Faculty of Agriculture, Sam Ratulangi University.Based on the results of the analysis, it shows that the organic matter content islow to moderate with the details that are in the low category, namely: In the 50-100 cmlayer -and> 100 cm the upper slope of the clove plant is 1.80% -1.20%, the nutmegplant is worth 1, 80%, and coconut plants worth 1.92%. The middle slope of the cloveplant was 1.80% -1.20%, the nutmeg plant was 1.20%, and the coconut plant was1.80%. The lower slope of the clove plant was 1.92% -1.68% -1.56%, the nutmeg plantwas 1.80% -1.20%, and the coconut plant was 1.56%. And in the medium category,namely: In layers 0-50 cm and 50-100 cm, the upper slope of the clove plant is 3.95%,the nutmeg is 3.59% -2.99%, and the coconut plant is 3.71% - 2.40%. The middle slopeof the clove plant was 3.59%, the nutmeg plant was 3.95% -3.35%, and the coconutplant was 2.99% -2.40%. The lower slope of the nutmeg plant is 3.11%, and under thecoconut plant it is 3.95% -2.04%.Keywords: Analysis of organic matter